Coral Reefs of the USA - Riegl, Bernhard M. (Springer, 2017)
Coral Reefs of the USA provides a complete overview of the present status of knowledge regarding all coral reef areas within the USA and its territories. It is written by the most experienced authorities in their fields and geographic areas. Stretching from the Caribbean to the western Pacific, the coral reefs of the USA span extensive geographic and biotic diversity, occur in a wide variety of geomorphological settings, and provide a representative cross-section of Holocene reef-building. This book will therefore be of broad general interest. For the first time, complete scholarly reviews are given for the geology, geomorphology and the biology of reefs encompassing a vast area stretching from the Mariana Islands in the west, Samoa in the south, Hawaii in the north and the Virgin Islands in the east. This book is not a status report, but will provide up-to-date information about stressors and the biotic responses of the reefs, as well as the geological explanations why these reefs exist in the first place. It will be an invaluable baseline-reference for all those who are engaged in research or management of these coral reefs or to those who simply enjoy being well-informed about one of the most iconic ecosystems of the USA.